Axial Inlet Geometry Effects on the Flow Structures in a Cyclone Burner Related to the Combustion Performance of Biomass Particles - Pasymi, P.; Budhi, Yogi Wibisono; Bindar, Yazid (Journal of Engineering and Technological Sciences, 2018)
Solid fuel combustion is always preceded by chemical decomposition. This process is largely determined by the flow structure and affected by the geometry and operating conditions of the combustion chamber. This study aimed to investigate the effect of relative axial inlet diameter (Dai//Dbc) on the flow structure in the proposed cyclone burner. The flow structure was determined with the standard k-e turbulent model using the Ansys-Fluent software. From the simulation results it was concluded that with all the axial inlet diameters used an integrated vortex formed in the center of the burner cylinder. The integrated vortex consisted of two vortices, namely a primary vortex and a secondary vortex. The primary vortex penetrated from the furnace box to the burner cylinder, while the secondary vortex was formed in the burner cylinder itself. There were two integration patterns from the primary vortex and the secondary vortex, namely a summation pattern and a multilayer pattern. The presence of a vortex in the center of the burner cylinder is allegedly responsible for an increase in the degree of mixing and pressure drop in that zone. The flow structure induced from the proposed burner had high symmetricity and was largely determined by the burner’s axial inlet diameter.